2010
DOI: 10.2147/tacg.s8794
|View full text |Cite
|
Sign up to set email alerts
|

Congenital malformations in Ecuadorian children: urgent need to create a National Registry of Birth Defects

Abstract: Aim: This study sets out (a) to estimate the prevalence of admissions by birth defects, using the official database of hospitals of Ecuador; and (b) to set the basis for a new National Register of Birth Defects in Ecuador that works as a program for the clinical and epidemiological investigation of risk factors in the etiology of congenital anomalies in Ecuadorian hospitals, using a case-control methodological approach. This is the first report in their class. Methods:The data used in this study are derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Among the OFCs, unilateral cleft lip was the most frequently observed defect in this study. These results are in agreement with the findings carried out in Ecuador by Gonzalez-Andrade and Lopez-Pulles [ 30 ]. In contrast to our findings, other studies conducted in Romania found higher prevalence of congenital heart defects (33.06%), followed by respiratory tract defects [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Among the OFCs, unilateral cleft lip was the most frequently observed defect in this study. These results are in agreement with the findings carried out in Ecuador by Gonzalez-Andrade and Lopez-Pulles [ 30 ]. In contrast to our findings, other studies conducted in Romania found higher prevalence of congenital heart defects (33.06%), followed by respiratory tract defects [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…, 2010; Galera et al. , 2010; González‐Andrade & López‐Pulles, 2010), and only one investigated micropenis (Silva et al. , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Neonates with such unrecognized critical congenital heart disease (CCHD) can manifest with growth retardation, heart failure, cardiovascular collapse, hypoxicischemic encephalopathy and even death. Early detection has led to a decline in poor postoperative outcome due to CCHD 2,3 .…”
Section: Introductionmentioning
confidence: 99%